Clinical Finding and Thyroid Function in Women with Struma Ovarii. (23rd May 2013) - Hosseini, Ali; Moeini, Aida
Abstract : Background . Struma ovarii (SO) is a variant of dermoid tumors which completely or mainly composed of thyroid tissues. Objective . We report our experience in the diagnosis and thyroid function of patients with SO in our hospital and also review the management and treatment option of this tumor. Materials and Methods . Between 2000 and 2012, 15 consecutive females with SO who were presented to our hospital were fully assessed. All women had histologically confirmed struma ovarii. The medical records of all patients including presenting symptoms, CT scan finding, and hormonal levels were collected for final analysis. Results . Average patient age was 36.6 years (ranging from 21 to 69). The mean ± SDs of serum TSH, T4, and T3 were2.16 ± 2.4  mUI/mL, 6.21 ± 3.74  ng/dL, and82.1 ± 40.5  ng/dL, respectively. The value of TSH was lower than normal value in 26.7%. Also, antithyroglobulin and anti-TPO were positive in 2 and one cases, respectively. Conclusion . Based on our data, it is more likely to see a disturbance in serum values of thyroid function test in women with SO.